2010
DOI: 10.4155/fmc.10.179
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Modulators of Inward Rectifier K + Channels: Recent Advances and Future Possibilities

Abstract: Inward rectifier potassium (Kir) channels have been postulated as therapeutic targets for several common disorders including hypertension, cardiac arrhythmias and pain. With few exceptions, however, the small-molecule pharmacology of this family is limited to nonselective cardiovascular and neurologic drugs with off-target activity toward inward rectifiers. Consequently, the actual therapeutic potential and 'drugability' of most Kir channels has not yet been determined experimentally. The purpose of this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 115 publications
1
60
0
Order By: Relevance
“…Thus, G protein-mediated inwardly rectifying potassium channels, also known as Kir channels, preferentially conduct K + ions inwardly under voltage-clamp conditions. 27 The GIRK2/Kir3.2 channel in brain is coupled to GABA B R pre-and postsynaptically, 10,13 and also is activated by GHB through the GABA B R. [28][29][30] Upon stimulating the GABA B R, the G-bɣ subunit detaches and moves to the neighboring Girk channel to activate it. 31,32 Thus, by administering GABA B agonists, we were able to indirectly test the activity of the Girk2 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, G protein-mediated inwardly rectifying potassium channels, also known as Kir channels, preferentially conduct K + ions inwardly under voltage-clamp conditions. 27 The GIRK2/Kir3.2 channel in brain is coupled to GABA B R pre-and postsynaptically, 10,13 and also is activated by GHB through the GABA B R. [28][29][30] Upon stimulating the GABA B R, the G-bɣ subunit detaches and moves to the neighboring Girk channel to activate it. 31,32 Thus, by administering GABA B agonists, we were able to indirectly test the activity of the Girk2 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Since Ho et al (1993) and Zhou et al (1994) cloned ROMK nearly 20 years ago, the small-molecule pharmacology of the Kir family has remained largely undeveloped and limited to barium, cesium, and a handful of nonselective drugs exhibiting weak off-target activity toward Kir channels (for review, see Bhave et al, 2010). The slow progress in the field has hindered efforts to understand the physiology, clinical relevance, and therapeutic potential of certain Kir channels.…”
Section: Discussionmentioning
confidence: 99%
“…The slow kinetics is not consistent with the rapid, physical obstruction of open channels from the extracellular face of the channel. More likely, the slow kinetics suggests interactions of VU625 with intracellular parts of the channel protein, similar to the interaction of VU590 with mammalian Kir1.1, which first needs to cross the plasma membrane before it can block the intracellular pore of the channel (Bhave et al, 2010;Lewis et al, 2009). Alternatively, the slow kinetics may indicate that VU625 causes 1) C-type inactivation by deforming the selectivity filter of the channel and therefore impeding the passage of K þ (Sepulveda et al, 2015), and/or 2) disruptions in Kir channel activity by interfering with the channel gating that is regulated by agents such as PIP 2 , G proteins, and intracellular pH (Sepulveda et al, 2015).…”
Section: Barium and Vu625: Different Mechanisms Of Action?mentioning
confidence: 94%
“…13) and pharmacology. VU590 was originally discovered in a highthroughput screen for modulators of mammalian Kir1.1 channels (Lewis et al, 2009), and has been shown to inhibit mammalian Kir1.1 and Kir 7.1 channels by blocking the intracellular pore near the selectivity filter of these channels (Bhave et al, 2010;Lewis et al, 2009). In spite of its marked structural differences from VU625, VU590 also inhibits AeKir1 channels expressed in HEK-293 cells and Xenopus oocytes, but not AeKir2B channels expressed in Xenopus oocytes .…”
Section: What Is the Function Of Aekir3?mentioning
confidence: 95%